Deep Insight of Design, Mechanism, and Cancer Theranostic Strategy of Nanozymes - Yang, Lu; Dong, Shuming; Gai, Shili; Yang, Dan; Ding, He; Feng, Lili; Yang, Guixin; Rehman, Ziaur; Yang, Piaoping (Nano-Micro Letters, 2023)
Since the discovery of enzyme-like activity of Fe3O4 nanoparticles in 2007, nanozymes are becoming the promising substitutes for natural enzymes due to their advantages of high catalytic activity, low cost, mild reaction conditions, good stability, and suitable for large-scale production. Recently, with the cross fusion of nanomedicine and nanocatalysis, nanozyme-based theranostic strategies attract great attention, since the enzymatic reactions can be triggered in the tumor microenvironment to achieve good curative effect with substrate specificity and low side effects. Thus, various nanozymes have been developed and used for tumor therapy. In this review, more than 270 research articles are discussed systematically to present progress in the past five years. First, the discovery and development of nanozymes are summarized. Second, classification and catalytic mechanism of nanozymes are discussed. Third, activity prediction and rational design of nanozymes are focused by highlighting the methods of density functional theory, machine learning, biomimetic and chemical design. Then, synergistic theranostic strategy of nanozymes are introduced. Finally, current challenges and future prospects of nanozymes used for tumor theranostic are outlined, including selectivity, biosafety, repeatability and stability, in-depth catalytic mechanism, predicting and evaluating activities. Highlights: 1 Classification and catalytic mechanism of nanozymes with different mimicking activities are dissertated. 2 Activity prediction and rational design methods of nanozymes are highlighted, including density functional theory, machine learning, biomimetic and chemical design. 3 The roles of nanozymes in different synergistic theranostic strategies for tumor are summarized and explained by representative examples in the past five years.